Islamic Religiosity and Future Anxiety on Disabled Children’s Parents: Parental Acceptance as a Mediating Variable - Gumelar Ferdiansyah Pratama; Herdian; Nur'aeni; Suwarti (Indigenous: Jurnal Ilmiah Psikologi, 2024)
The birth of a child with special needs introduces a myriad of challenges, triggering complex psychological dynamics in parents that significantly influence their anxieties about the child's future. This research aims to delve into this intricate phenomenon by examining the role of parental acceptance as a mediator in the impact of Islamic religiosity on future anxiety among parents of children with special needs. The study involved 115 parents (46 fathers and 69 mothers) of children with special needs at SLBN Tasikmalaya, selected through purposive sampling. Data collection was executed through the administration of research questionnaires. The analytical framework employed path analysis, an integrated method amalgamating regression analysis and mediation analysis, facilitated by the use of SPSS application version 25. The calculated results revealed that Islamic religiosity exerts an indirect effect, assuaging future anxiety through the mediating influence of parental acceptance. These findings underscore the significant role of parental acceptance in mediating the impact of Islamic religiosity and its potential to contribute to the reduction of future anxiety. Consequently, the study advocates for the implementation of targeted programs aimed at promoting Islamic religiosity and fostering parental acceptance, providing a strategic avenue to mitigate the enduring impacts of future anxiety within this demographic.